A phonologically calibrated acoustic dissimilarity measure - Kochanski, G; Baghai-Ravary, L; Coleman, J (2010)
One of the most basic comparisons between objects is to ask how similar they are. Linguistics and phonology are founded on this question. The classic definitions of phonemes and features involve contrast between minimal pairs. A minimal pair of words requires that there be two sounds that are dissimilar enough for the words to be considered different. Otherwise we wouldn't speak of a minimal pair of words but rather of a single word with two meanings. Likewise, phonetic similarity is needed to group together separate instances into a single word or sound. Without some intuition about which sounds are so similar that they should be treated as instances of the same linguistic object, the field would be no more than a collection of trillions of disconnected examples. So, it is important to have a measure of dissimilarity between sounds. Some exist already: e.g. measures of dissimilarity between the input and output of speech codecs have been used as a way of quantifying their performance (e.g. Gray, Gray, and Masuyama 1980). Cepstral distance has been frequently used, and the Itakura-Saito divergence is also widely used. But, none of these have been explicitly calibrated against the differences in speech that are important to human language. In this paper, we do so.